تطبيق إدارة المعرفة بالجامعات الليبية لتحقيق التميز في البحث العلمي (Albayan Scientific Journal, 2023)
Knowledge has become a driving force for the economy and social progress, and the effective weapon of any institution if managed well. Hence, the importance of knowledge management, which is based on organizing the institutions' expertise, skills and knowledge, to help them achieve their goals, Innovation The mission of universities in the present era is no longer limited to traditional objectives. The message extended to all aspects of scientific, technical and technological life. This made the most important duties of modern universities to interact with the society to discuss its needs and requirements, High rankings in innovation and technological and technological progress And this is only by activating the scientific research movement, and opening channels of cooperation and coordination and communication between universities and different sectors of development. In this sense, this research aims at clarifying the concept of knowledge management and its objectives in universities And the knowledge of the role of knowledge management in achieving excellence in scientific research, and monitoring the experiences of some universities in other countries in the field of knowledge management. The results of the research revealed the challenges facing Libyan universities in the application of knowledge management linked to financial aspects Technical and organizational The research recommended a set of recommendations through which knowledge management in Libyan universities can be applied to achieve excellence in scientific research